The present condition and outlook for hydrogen-natural gas blending technology - Chae, M. J.; Kim, J. H.; Moon, B.; Park, S.; Lee, Y. S.
Korea's economy should develop a safe and cost-effective hydrogen transport system to realize the hydrogen economy. Among the methods of hydrogen transport, pipelines are the only feasible means of achieving cost-effective and safe transport over longer distances. This technical report proposes a method that would allow for using existing natural gas pipelines to transport mixed gas (hydrogen-natural gas). The properties of the mixed gas, the durability of the pipeline caused by hydrogen embrittlement, and gas loss from leakage are reviewed according to the hydrogen ratio. In addition, several separation methods of mixed gas are introduced. From the survey of international research or pilot projects, if hydrogen is blended with a concentration less than 20 percent, that does not significantly affect gas quality, safety, risk, materials, and network capacity. This study also suggests the suitable hydrogen supply methods for domestic use.
Keywords: HYDROGEN; BLENDING RATIO; PIPELINE; EMBRITTLEMENT; LEAKAGE